2020
DOI: 10.1016/j.chemosphere.2019.124921
|View full text |Cite
|
Sign up to set email alerts
|

Formation of phenoxy-type Environmental Persistent Free Radicals (EPFRs) from dissociative adsorption of phenol on Cu/Fe and their partial oxides

Abstract: The interplay of phenolic molecules with 3d transition metals, such as Fe and Cu, and their oxide surfaces, provide important fingerprints for environmental burdens associated with thermal recycling of e-waste and subsequent generation of notorious dioxins compounds and phenoxy-type Environmental Persistent Free Radicals (EPFRs). DRIFTS and EPR measurements established a strong interaction of the phenol molecule with transition metal oxides via synthesis of phenolic-and catecholic-type EPFRs intermediates. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…The existence of oxide of Cu was proven to be beneficial for the EPFR generation ( Yang et al, 2017b ). Intriguingly, the results of computational simulation elucidated Cu could mediate the formation of oxygen-centered EPFRs ( Ahmed et al, 2020 ), which may explain the occurrence of the same type of EPFRs in this work. Hence, the higher concentration of Cu might promote the Cu-mediated secondary formation of EPFRs in PM 2.5 , resulting in their unreduced contamination level during city lockdown in Linfen.…”
Section: Resultssupporting
confidence: 59%
“…The existence of oxide of Cu was proven to be beneficial for the EPFR generation ( Yang et al, 2017b ). Intriguingly, the results of computational simulation elucidated Cu could mediate the formation of oxygen-centered EPFRs ( Ahmed et al, 2020 ), which may explain the occurrence of the same type of EPFRs in this work. Hence, the higher concentration of Cu might promote the Cu-mediated secondary formation of EPFRs in PM 2.5 , resulting in their unreduced contamination level during city lockdown in Linfen.…”
Section: Resultssupporting
confidence: 59%
“…Phenolic common derivatives such as Bisphenol A (BPA), chlorophenols (CPs), and phenolic endocrine disrupting compounds (EDCs) are often listed at the top of lists of environmental pollutants. Phenolic compounds and their halogenated derivatives can also produce dioxin compounds [40]. Dioxins are notorious for their persistency in the environment and their high toxicity, so much so that they usually are at the top of "dirty dozen" lists.…”
Section: Environmental Fate and Treatment Of Phenolic Compoundsmentioning
confidence: 99%
“…Incomplete combustion of organic materials, such as fuel and biomass, provides the main source of EPFRs. Previous studies have reported EPFR concentrations of 10 16 to 10 18 spins g –1 in various samples, including cigarette smoke, biochars, coal, electronic waste, residential and vehicle fuel, and industrial activity. , The organic substituents in these materials can also react during combustion and form a variety of fused, multi-ringed aromatic compounds known as polycyclic aromatic hydrocarbons (PAHs). ,, The formation of PAHs has been previously explained by various reaction pathways, e.g., hydrogen abstraction acetylene addition, hydrogen abstraction vinylacetylene addition, and methyl addition cyclization. , These pathways involve free radical reactions, which can form other free radical molecules. Due to the aromaticity of the PAH present in combustion particles, the resulting free radicals become resonance-stabilized in the structure of the particles. ,,,,,,, Because PAHs are ubiquitous in combustion particles, PAHs and PAH-derived EPFRs can be transported into the body and lodged in the heart and lungs, contributing to chronic disease, cardiopulmonary dysfunction, and a decrease in life expectancy. ,, …”
Section: Introductionmentioning
confidence: 99%